PROJECTS SUPPORTED BY STRUCTURAL FUNDS OF EU REALIZED AT UNIVERSITY OF ŽILINA IN COOPERATION WITH AIR TRANSPORT DEPARTMENT AND FLIGHT TRAINING ORGANIZATION – AIR SCHOOL OF THE UNIVERSITY OF ŽILINA (Perner's Contacts, 2011)
This paper is about projects of University of Žilina (especially projects which are realized at Air Transport Department in cooperation with Flight Training Organization (FTO) – Air School of the University of Zilina) and are supported and co-financed by structural founds of EU. At this moment the Air Transport Department deals with three projects: Implementation of science-research knowledge to the Air Transport -ITMS 26220220010, Centre of excellence for Air Transport -ITMS 26220120065, Q Brokerage centre of Air Transport for Transfer of Technology and knowledge into Transport and Transport Infrastructure- ITMS 26220220156.